Type of school as determinant of dental care-seeking behavior among adolescents in Mangalore Taluk: A cross-sectional study - Rekha P Shenoy; T A Abdul Salam; Reema Agrawal (Wolters Kluwer Medknow Publications, 2018)
Background: The influence of location and type of school on dental care seeking behavior has not been adequately investigated. The objectives of this investigation were to determine whether the location and type of school enrolled in influenced dental care-seeking behavior among school-going adolescents. Materials and Methods: Public and private high schools in urban and rural areas of Mangalore taluk were selected through stratified cluster sampling. Sample size was determined to be 1340; after obtaining necessary permissions, data were collected on dental treatment obtained in the past, details of obtained treatment, facility where treatment was obtained, and its distance from place of residence from students who fulfilled the inclusion criteria. The Chi-squared test was used for analysis with the significance level set at P < 0.05. Results: Dental treatment history was reported by 35.6% respondents. More private schoolchildren had obtained dental care (P = 0.005). Restorative care was most frequent treatment modality obtained. Higher number of private school students received treatment at dental clinics, while public and rural schoolchildren seemed to prefer dental schools (P < 0.001). More private and rural schoolchildren traveled more than 5 km to obtain dental care (P < 0.05). Conclusions: Children enrolled in private and rural schools formed a large component of those who had obtained dental care, were more likely to obtain restorative treatment, and traveled considerable distances to obtain care.